2020
DOI: 10.1016/j.tree.2020.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel Organisation of Animal Sociality

Abstract: Multilevel societies (MLSs)-stable nuclear social units within a larger collective encompassing multiple nested social levels-occur in several mammalian lineages. Their architectural complexity and size impose specific demands on their members requiring adaptive solutions in multiple domains. The functional significance of MLSs lies in their members being equipped to reap the benefits of multiple group sizes. Here we propose a unifying terminology and operational definition of MLS. To identify new avenues for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
127
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 109 publications
(129 citation statements)
references
References 102 publications
2
127
0
Order By: Relevance
“…Vulturine guineafowl live in a multilevel society, where groups preferentially associate with other groups ( Papageorgiou et al, 2019 ). In such societies, intergroup associations can bring many important benefits, such as information sharing on predators and resources, as well as mating and dispersal opportunities ( Grueter et al, 2020 ). A large home range size in a multilevel society could provide groups with access to more communal roosts (we have observed up to five groups in a single roost, Papageorgiou et al, 2019 ) and more glades, and thus more opportunities to associate with more groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vulturine guineafowl live in a multilevel society, where groups preferentially associate with other groups ( Papageorgiou et al, 2019 ). In such societies, intergroup associations can bring many important benefits, such as information sharing on predators and resources, as well as mating and dispersal opportunities ( Grueter et al, 2020 ). A large home range size in a multilevel society could provide groups with access to more communal roosts (we have observed up to five groups in a single roost, Papageorgiou et al, 2019 ) and more glades, and thus more opportunities to associate with more groups.…”
Section: Discussionmentioning
confidence: 99%
“…In such species, groups can interact affiliatively and preferentially with specific other groups, resulting in a multilevel society. In such societies, having a larger home-range size might generate more chances to associate with conspecifics from other groups ( Grueter et al, 2020 ), which, in turn, can increase mating opportunities (by increasing contact with members of the opposite sex; Grueter et al, 2015 ), dispersal opportunities (as sub-adults often disperse to neighbouring groups; Städele et al, 2015 ) and information sharing about food resources or predation risk ( Whitehead et al, 2012 ). Thus, there are many ways that groups can benefit from maximizing their space use, up to the point where the costs of travel and navigation do not override the benefits gained.…”
Section: Introductionmentioning
confidence: 99%
“…Some females have sexual experienced with other resident male int the band, this might also offer her and her unweaned infant a refuge when there is high risk of infanticide. In addition, food competition among the band member in this species is low because ubiquitous lichens and leaves form a major dietary constituent throughout the year (Li 2006), facilitating units to be in close proximity to potentially reduce predatory attacks through travelling, feeding, and resting within the same areas (Grueter et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the insight that the trade-off between current and future reproduction, animal personalities could be given an adaptive explain in polymorphic population (Wolf et al 2007). In snub-nosed golden monkeys of a multilevel society, where multiple OMUs coordinate and forage together as one larger social band (Grueter et al 2020), social complexity would allow polymorphic personality of resident male in the band. In this study, we have observed two kinds of male personalities towards unweaned infants following male replacement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation